LEXICAL AND GRAMMATICAL FEATURES OF GRAMMATICAL COMPRESSION IN ENGLISH AND UZBEK MASS MEDIA - Turg’unova Fazilat Rustam qizi (Sciental Journals Publishing, 2025)
This article explores the lexical and grammatical features of grammatical compression in English and Uzbek. The study focuses on methods of grammatical compression in the mass media of both languages, implemented through abbreviations, acronyms, and simplification of word combinations. In English, grammatical compression is primarily achieved through the use of abbreviations and acronyms, whereas in Uzbek it is more closely related to lexical reduction and the simplification of multi-word expressions. The article aims to analyze the significance of grammatical compression within the contexts of linguistics, communication, and culture, as well as its impact on language systems. The research findings highlight distinctive characteristics of English and Uzbek, shedding light on their respective sociocultural factors and illustrating dynamic changes in language systems.
Keywords: Grammatical compression, lexical features, grammatical features, English language, Uzbek language, abbreviations, acronyms, mass media, syntactic structure, semantic meaning, linguistics, communication, cultural characteristics.